PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT BORNEO SENTANA GEMILANG BALIKPAPAN - Emannuel Tanod, Graciela; Ariani, Misna; Arrywibowo, Imam (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
The purpose of this study was to determine the effect of Work Environmet, Motivation, and Work Discipline on Employee Job Satisfaction at PT Borneo Sentana Gemilang Balikpapan. The type of this study used is quantitative research. The sampling technique in this study was purposive sampling with a sample 31 employees at PT Borneo Sentana Gemilang Balikpapan. Methods of data collection is done by distributing questionnaires. This study uses SmartPLS to processing data. The results of this study indicate that the work environment variable has a positive and insignificant effect on employee job satisfaction PT Borneo Sentana Gemilang Balikpapan. Motivation variable has a significant effect on employee job satisfaction PT Borneo Sentana Gemilang Balikpapan. And work discipline variable has a positive and insignificant effect on employee job satisfaction PT Borneo Sentana Gemilang Balikpapan.